Pemberian Sanksi bagi Anak Korban Perkosaan Incest yang Melakukan Aborsi (Studi Kasus Putusan Nomor : 5/Pid.Sus-Anak/2018/PN.MBN) - Dinda Tania Wardani; Anajeng Esri Edhil Mahanani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Kids are the following technology of the country whose rights have to be included, the state has provided a legal umbrella as stipulated in regulation wide variety 23 of 2002 regarding child safety, and regulation wide variety 11 of 2012 regarding the kid crook Justice device. In the current era, there are many problems in Indonesia related to children as victims of sexual crimes where children must be protected, especially as victims and have not been able to account for the law. One of which is in the districtl court docket range : l5/Pid.Sus-child/2018/PN.MBNl the case of the crime of abortion. A 15 year old child is sentenced to commit an abortion against a child in the womb, a child has an abortion due to an 18 year old sibling. The punishment given by the judge to a child victim of rape is contrary to Article forty eight of the crook Code. Where a children sufferer of rape is requested to be held criminally accountable. consequently, this have a look at will speak a way to modify abortion from rape in step with fine regulation in Indonesia, the way to shield kids who are abortionists on account of incestuous rape.The approach used on this examine is a normative juridical approach. This research data was obtained through primary data, namely the decision of the district court number: 5/Pid.Sus-Child/2018/PN.MBN. This research aims to present a situation or formulate a problem according to the available data. Therefore it is clear that this study (Study Number: 5/Pid.Sus-Anak/2018/PN.MBN) uses normative legal procedures with the aim of obtaining a clear picture regarding the judicial review of criminal convictions against minors who are victims of criminal acts incestuous rape who underwent an abortion.Thel effects of thisl take a look at imply that the selection wide variety : 5/Pid.Sus-child/2018/PN.MBN is still contradictory, a child who is still 15 years old is sentenced to commit the crime of abortion against a child in the womb. The child had an abortion because of his older brother. The punishment given by the judge to a child victim of rape is contrary to Article forty eight of the crook Code. In which a child sufferer of rape is asked to be held criminally responsible